Karakter Kristus dalam Dinamika Kehidupan Modern: Tinjauan Teologis-Etis terhadap Krisis Karakter di Era Disrupsi Digital - Tjipto Santoso Subagio (Sekolah Tinggi Teologi Bethel Ambon, 2025)
The development of digital technology and social acceleration in the modern era has significantly transformed human lifestyles, ways of thinking, and character formation. However, behind this progress emerge various moral and spiritual crises such as instant culture, digital narcissism, post-truth relativism, identity fragmentation, and existential exhaustion. This study aims to examine the character of Christ as a theological-ethical paradigm in responding to the crisis of character in the era of digital disruption. The research employs a qualitative method with a library research approach through theological analysis of biblical texts, theological literature, and empirical data related to contemporary digital social phenomena. The findings reveal that the character of Christ, centered on kenosis, integrity of truth, love, and relational spirituality, provides a relevant ethical foundation for modern humanity experiencing identity disorientation and character degradation. Christ is not merely a moral example, but the model of true humanity who restores the meaning of the imago Dei within human beings. This study affirms that the formation of Christlike character is an urgent necessity for the church and modern society so that individuals may live authentically, maintain integrity in digital spaces, and grow in spiritual maturity amid disruptive cultural changes.